2009
DOI: 10.1007/s10165-009-0168-y
|View full text |Cite
|
Sign up to set email alerts
|

Hydralazine-induced autoimmune disease: comparison to idiopathic lupus and ANCA-positive vasculitis

Abstract: We report two cases of hydralazine-induced vasculitis with rare complications: pulmonary renal syndrome and digital gangrene. We also review 68 published cases of hydralazine-induced vasculitis. Hydralazine-induced vasculitis mimics idiopathic antineutrophil cytoplasmic antibody (ANCA)-positive vasculitis. However, it also produces other autoantibodies, such as antinuclear antibodies, antihistone antibodies, anti-dsDNA antibodies, and antiphospholipid antibodies. Patients with hydralazine-induced vasculitis ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 34 publications
2
82
0
1
Order By: Relevance
“…Evidence for hydralazine-associated vasculitis dates to the pre-ANCA era, including rapidly progressive GN. A 2009 review of the literature found 68 hydralazine vasculitis reports (mean duration of drug exposure 54.7 years; mean dose 5142 mg/d) (38). Similar to the findings by Choi et al (5), kidney disease was common on presentation (81%), and patients had additional serologic evidence of an autoimmune process (96% ANA positive, 26% anti-dsDNA antibody positive, and 44% hypocomplementemia).…”
Section: Drugs Associated With Aavsupporting
confidence: 67%
“…Evidence for hydralazine-associated vasculitis dates to the pre-ANCA era, including rapidly progressive GN. A 2009 review of the literature found 68 hydralazine vasculitis reports (mean duration of drug exposure 54.7 years; mean dose 5142 mg/d) (38). Similar to the findings by Choi et al (5), kidney disease was common on presentation (81%), and patients had additional serologic evidence of an autoimmune process (96% ANA positive, 26% anti-dsDNA antibody positive, and 44% hypocomplementemia).…”
Section: Drugs Associated With Aavsupporting
confidence: 67%
“…Hydralazine-induced vasculitis mimics idiopathic anti-neutrophil cytoplasmic antibody-positive vasculitis, presenting as pulmonary or renal vasculitis and gangrene [119][120][121]. Toxic epidermal necrolysis has been reported, with recurrence following the reintroduction of hydralazine [122].…”
Section: Miscellaneous Agentsmentioning
confidence: 99%
“…In contrast to hydralazine-induced lupus, hydralazine-induced vasculitis can be severe with frequent involvement of the kidneys. Hydralazine-induced vasculitis involving the skin was first reported in 1980, and vasculitis involving the kidneys was first suspected in 1981 (5,6). Cases of rapidly progressive glomerulonephritis were reported in 1983, and subsequently, ANCA positivity was demonstrated in some of these cases (7,8).…”
Section: Introductionmentioning
confidence: 99%